Realizing nutrition equity in urban food systems - Darcy A. Freedman Darcy A. Freedman; Morgan Taggart; Michael Walton; Linea Webb; Ismail Samad; Don Gaddis; Carol White; Shirley Bell-Wheeler; Dawn Glasco; Owusua Yamoah; Emily Nelson (Journal of Agriculture, Food Systems, and Community Development)
Commonly used measures for assessing local food systems, such as food security or healthy food access, do not provide guidance into the series of actions involved in transforming these outcomes. To address this gap, our research brief presents lessons learned from a community action research project about implementation mechanisms (i.e., series of linked actions) involved in community-led efforts to transform urban food systems to achieve goals of nutrition equity. Our data are derived from the perceptions of 18 community leaders identifying as Black, Indigenous, and People of Color (BIPOC) planning to implement food justice initiatives in Cleveland, Ohio, United States. Content analysis revealed 10 themes and related indicators reflecting mechanisms of implementation and impact of community-led food justice initiatives. Findings underscore the importance of implementation mechanisms that influence changes in community power, food culture and norms, and healthy food retail while mitigating risks of gentrification. Future research is needed to operationalize these mechanisms of implementation to provide guidance for action planning, decision-making, and accountability within urban food systems.